C-MCG: Synthesis, Uptake Selectivity, and Primate PET of a Probe for Glutamate Carboxypeptidase II (NAALADase) - Martin G. Pomper; John L. Musachio; Jiazhong Zhang; Ursula Scheffel; Yun Zhou; John Hilton; Atul Maini; Robert F. Dannals; Dean F. Wong; Alan P. Kozikowski (Molecular Imaging, 2002)
Imaging of glutamate carboxypeptidase II (GCP II), also known as N -acetylated α-linked l -amino dipeptidase (NAALADase), may enable study of glutamatergic transmission, prostate cancer, and tumor neovasculature in vivo. Our goal was to develop a probe for GCP II for use with positron emission tomography (PET). Radiosynthesis of 11 C–MeCys–C(O)–Glu or 11 C-( S )-2-[3-(( R )-1-carboxy-2-methylsulfanyl-ethyl)-ureido]-pentanedioic acid ( 11 C-MCG), an asymmetric urea and potent ( K i = 1.9 nM) inhibitor of GCP II, was performed by C-11 methylation of the free thiol. Biodistribution of 11 C-MCG was assayed in mice, and quantitative PET was performed in a baboon. 11 C-MCG was obtained in 16% radiochemical yield at the end of synthesis with specific radioactivities over 167 GBq/mmol (4000 Ci/mmol) within 30 min after the end of bombardment. At 30 min postinjection, 11 C-MCG showed 33.0 ± 5.1%, 0.4 ± 0.1%, and 1.1 ± 0.2% ID/g in mouse kidney (target tissue), muscle, and blood, respectively. Little radioactivity gained access to the brain. Blockade with unlabeled MCG or 2-(phosphonomethyl)pentanedioic acid (PMPA), another potent inhibitor of GCP II, provided sevenfold and threefold reductions, respectively, in binding to target tissue. For PET, distribution volumes (DVs) were 1.38 then 0.87 pre- and postblocker (PMPA). Little metabolism of 11 C-MCG occurred in the mouse or baboon. These results suggest that 11 C-MCG may be useful for imaging GCP II in the periphery.